Perceptions of Sports Science Students at Yogyakarta State University on Interest and Motivation to Learn SCUBA Diving - Muhamad Nanang Solikhin; Sumaryanti Sumaryanti; Sulistiyono Sulistiyono; Fauzi Fauzi (Jorpres (Jurnal Olahraga Prestasi), 2023)
The scope of sports as stated in Indonesian Law no. 3 of 2005, concerning the National Sports System includes three pillars, namely sports education, recreational sports, and achievement sports. Students' interest and motivation to study types of fun recreational sports and students develop competencies/skills that can enable future professional opportunities to become an important part of the consideration in diving at the Faculty of Sports Science, Yogyakarta State University. The method used in this research is a survey using a questionnaire. The questionnaire used includes a closed-end questionnaire, in which the respondent chooses the alternative answers that have been provided. The research respondents were 19 students who volunteered in the diving learning model test. Research on student perceptions of diving is very much needed as a basis for understanding diving as a whole. The results of the study obtained the Perception value of students of the Faculty of Sports Science, Yogyakarta State University about learning the sport of Scuba Diving "on the aspect of interest in learning. The results of the statistical analysis for the coefficient of determination,  adjusted R-square value is 0.618 (61,8%). This means that the ability of the independent variables (Learning interest and Study Motivation)  in this study affects the dependent variable (Perception) by 61,8%.  Furthermore based on the F test results F count is  16,385 F table 3,49.  This means that the independent variables (Learning interest and Study Motivation) simultaneously Influence affects to the dependent variable (student perceptions )about learning SCUBA diving.